The Teachers’ Perception of Activity-Based Tasks Integrated with Utilization of Web-Based Familiar Topics - Maming, Khadijah; Sudarmanto; Yusmah (University of Surakarta, 2025)
This research explores teachers' perceptions of activity-based tasks integrated with web-based familiar topics as an instructional model for English language teaching. It is oriented on activity-based language instruction tasks as one of the development models of the content-based instruction (CBI) approach. The participants of this research were ten English teachers. The questionnaire was used to obtain the research data regarding the teachers’ perceptions. The teachers showed their positive responses to activity-based tasks integrated with web-based familiar topics. The teachers commented positively that these tasks potentially trained them to utilize and organize learning materials into a sequence of interactive learning activities. Then, they perceived positively that activity-based tasks reinforced cooperative learning, empowered student-centered classroom activities, and created experiential learning. Similarly, the students expressed interest in learning English through theme-based tasks. It made an enjoyable learning atmosphere, allowed them to acquire meaningful learning experiences, fostered their oral and written English practice, and encouraged their active participation in the English learning class.